Intraocular Gnathostomiasis: A rare Case Report of a Live Intravitreal Worm - Anuja Mohanty; Santosh Kumar Mahapatra (Delhi Journal of Ophthalmology)
We report a rare case of intraocular gnathostomiasis from eastern India. A 32 year old male from Cuttack, Odisha presented to us with decreased vision in his left eye of counting fingers(CF) at 2 metres since 1 week without any pain, lid edema or periorbital swelling. Anterior segment was normal. Indirect ophthalmoscopy revealed a live motile worm in posterior vitreous cavity near macula. The worm was removed via pars plana vitrectomy. The removal was first attempted using flute needle but in vain and was finally done with end-grasping forceps. Microscopy revealed Gnathostoma spinigerum. The patient was treated with oral albendazole and steroids. The case is reported because of its rarity.